KEPATUHAN PAJAK DAN TATA KELOLA PERPAJAKAN BAGI UMKM DI INDONESIA: KAJIAN PUSTAKA TERHADAP REGULASI, IMPLEMENTASI, DAN TANTANGAN - Loso Judijanto; Al-Amin (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study examines tax compliance and tax governance for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a literature review of regulations, implementation, and challenges faced. This study explains how simplified tax regulations and a presumptive tax system are applied to improve MSME compliance while supporting the growth of this sector in the national economy. However, various challenges such as low tax literacy, complicated administrative processes, and technological limitations remain major obstacles to policy implementation. This research highlights the importance of responsive and inclusive tax governance, as well as the need for improved education and assistance for MSME actors to achieve better tax compliance. The results of this study provide a basis for strategic recommendations to strengthen the MSME taxation system, which can increase their contribution to state revenue and business sustainability.